KONSEP METODE AL-MIFTAH LIL ULUM DALAM PEMBELAJARAN KITAB KUNING DI PESANTREN MULTIDIMENSI AL-FAKHRIYAH - Inayah, Nur; Tang, Muhammad; Mappatunru , Sakkirang (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Abstract Al-Miftah Lil Ulum method is a quick method for reading yellow books and introduced by the Sidogiri Islamic Boarding School, Pasuruan, East Java. This research aims to understand and analyze the concept of the al-Miftah Lil Ulum method in learning of yellow books at the Multidimensi Al-Fakhriyah Islamic Boarding School. The researcher used a qualitative research method with a case study approach. The data analysis adopted by the researcher follows the model proposed by Miles, Huberman, and Saldana namly data condensation, data presentation, and verification. The data validity techniques used were time triangulation, source triangulation, and technique triangulation. The results of the research show that the concept al-Miftah Lil Ulum method in learning of yellow books at theat the Multidimensi Al-Fakhriyah Islamic Boarding School is (1) engaging, as it incorporates various teaching methods, (2) creative, as the al-Miftah Lil Ulum material is an integration of various books with similar themes, (3) easy to understand because the abundance of examples and tables, and (4) enjoyable, as it includes nadhom in Indonesian and arranged with popular melodies.